2012
DOI: 10.1186/1865-1380-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial calcification in constrictive pericarditis

Abstract: BackgroundA high index of suspicion is required to make the diagnosis of constrictive pericarditis (CP) in patients presenting with cirrhosis and volume overload, as they can otherwise go misdiagnosed for years.MethodsCase report.FindingsA 51 year-old man with a history of presumed alcoholic cirrhosis presented to the emergency department with anasarca. Abdominal ultrasound with Doppler demonstrated a nodular cirrhotic liver, but no evidence of portal hypertension or ascites. The chest x-ray, however, was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Pericardial calcification should provide a clue to the diagnosis of constrictive pericarditis (see Figure 1 ). One case study demonstrated the importance of this finding on low-cost imaging to help point towards this diagnosis [ 9 ]. The major differential of constrictive pericarditis is restrictive cardiomyopathy which is more common in patients with sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial calcification should provide a clue to the diagnosis of constrictive pericarditis (see Figure 1 ). One case study demonstrated the importance of this finding on low-cost imaging to help point towards this diagnosis [ 9 ]. The major differential of constrictive pericarditis is restrictive cardiomyopathy which is more common in patients with sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%